PENGARUH FINANCIAL DISTRESS, LEVERAGE DAN FREE CASH FLOW TERHADAP MANAJEMEN LABA (Perusahaan Sektor Transportasi & Logistik di Bursa Efek Indonesia 2019-2021) - Devia Leoni Wandari (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
Earnings management is a manager's fraudulent behaviour to deceive stakeholders by changing the numbers in the financial statements. This study aims to determine the effect of financial distress, leverage and free cash flow on earnings management, both real and accrual earnings management. The research sample consisted of 21 companies from the transportation and logistics sector listed on the Indonesia Stock Exchange (IDX) for 2019-2021. Data analysis used panel data analysis with STATA 14.2. The study results show that simultaneously the independent variables affect Real Earnings Management and accruals. However, partially, financial distress (FD) and free cash flow (FCF) do not affect real earnings management (REM). The FD and FCF variables are not a factor causing managers to do REM or not to do REM, companies that experience financial distress or show low FCF numbers tend to focus on improving company performance. Leverage (LEV) has a positive effect on real earnings management. Companies with high LEV values show more outstanding debt than assets, so managers do REM to cover the company's debt figures. Financial distress and leverage do not affect accrual earnings management (AEM). Companies that experience financial distress or show high leverage make managers focus on overcoming these problems so that these two factors are not the main factors for managers to carry out AEM. Free cash flow harms accrual earnings management.